Supramolecular clustering of the cardiac sodium channel Nav1.5 in HEK293F cells, with and without the auxiliary β3‐subunit. Issue 3 (16th January 2020) - Salvage, Samantha C.; Rees, Johanna S.; McStea, Alexandra; Hirsch, Michael; Wang, Lin; Tynan, Christopher J.; Reed, Matthew W.; Irons, Jennifer R.; Butler, Richard; Thompson, Andrew J.; Martin-Fernandez, Marisa L.; Huang, Christopher L.‐H.; et al.
Abstract: Voltage‐gated sodium channels comprise an ion‐selective α‐subunit and one or more associated β‐subunits. The β3‐subunit (encoded by the SCN3B gene) is an important physiological regulator of the heart‐specific sodium channel, Nav1.5. We have previously shown that when expressed alone in HEK293F cells, the full‐length β3‐subunit forms trimers in the plasma membrane. We extend this result with biochemical assays and use the proximity ligation assay (PLA) to identify oligomeric β3‐subunits, not just at the plasma membrane, but throughout the secretory pathway. We then investigate the corresponding clustering properties of the α‐subunit and the effects upon these of the β3‐subunits. The oligomeric status of the Nav1.5 α‐subunit in vivo, with or without the β3‐subunit, has not been previously investigated. Using super‐resolution fluorescence imaging, we show that under conditions typically used in electrophysiological studies, the Nav1.5 α‐subunit assembles on the plasma membrane of HEK293F cells into spatially localized clusters rather than individual and randomly dispersed molecules. Quantitative analysis indicates that the β3‐subunit is not required for this clustering but β3 does significantly change the distribution of cluster sizes and nearest‐neighbor distances between Nav1.5 α‐subunits. However, when assayed by PLA, the β3‐subunit increases the number of PLA‐positive signals generated by anti‐(Nav1.5 α‐subunit) antibodies, mainly at the plasma membrane. Since PLA can be sensitive to the orientation of proteins within a cluster, we suggest that the β3‐subunit introduces a significant change in the relative alignment of individual Nav1.5 α‐subunits, but the clustering itself depends on other factors. We also show that these structural and higher‐order changes induced by the β3‐subunit do not alter the degree of electrophysiological gating cooperativity between Nav1.5 α‐subunits. Our data provide new insights into the role of the β3‐subunit and the supramolecular organization of sodium channels, in an important model cell system that is widely used to study Nav channel behavior.